2022
DOI: 10.1002/jbm.a.37435
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic freeze–thaw grinding to decellularize meniscus for fabricating porous, elastic scaffolds

Abstract: Decellularized meniscus extracellular matrix (dmECM)‐based biological scaffolds in the forms of sponge, hydrogel, nanofiber, and composite have gained increasing interest in meniscus tissue engineering and regeneration. A common shortcoming of those scaffolds is insufficient mechanical strength and poor elasticity. Herein, we report a practicable protocol for milder meniscus decellularization to prepare elastic, porous dmECM scaffolds. Porcine meniscus was pulverized by cyclic freeze–thaw grinding and then tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(231 reference statements)
0
9
0
Order By: Relevance
“…In order to further detect the regionally biochemical differences of hydrogels from different regions, Wu et al fabricated regionally decellularized meniscal ECM hydrogels with different (outer, middle, and inner) zones of porcine meniscus, and found that the cell-seeded outer meniscus (OM) hydrogel had a nine-fold increase in peak compressive strengths (18.3 ± 3.6 vs. 2.1 ± 0.1 kPa) and a six-fold increase in initial modulus (9.9 ± 2.6 vs. 1.7 ± 0.2 kPa), the cell-seeded middle meniscus (MM) hydrogel experienced a 21-fold increase in peak compressive strengths (27.1 ± 4.6 vs. 1.3 ± 0.1 kPa) and a nine-fold increase in initial modulus (6.7 ± 1.6 vs. 0.8 ± 0.1 kPa), the cell-seeded inner meniscus (IM) hydrogel achieved a 22-fold increase in peak compressive strengths (26.0 ± 3.0 vs. 1.2 ± 0.2 kPa) and a nine-fold increase in initial modulus (9.4 ± 1.8 vs. 0.9 ± 0.2 kPa) over the IM hydrogel only ( Wu et al, 2021 ). Ding et al compared the scaffold properties of native meniscus, untreated extracellular matris (ECM) and decellularized ECM (dmECM) from porcine meniscus, and found that both dmECM and untreated ECM scaffolds had lower compressive modulus than native meniscus (181 ± 63 kPa, p < 0.001) and the native meniscus was relatively very stiff and showed significantly higher failure compression stresses (2030 ± 250 kPa, p < 0.001) ( Ding Y. et al, 2022 ). From these two studies, it can be seen that although biological hydrogels can improve the mechanical strength by adding cells, they are still difficult to achieve the mechanical strength of normal meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…In order to further detect the regionally biochemical differences of hydrogels from different regions, Wu et al fabricated regionally decellularized meniscal ECM hydrogels with different (outer, middle, and inner) zones of porcine meniscus, and found that the cell-seeded outer meniscus (OM) hydrogel had a nine-fold increase in peak compressive strengths (18.3 ± 3.6 vs. 2.1 ± 0.1 kPa) and a six-fold increase in initial modulus (9.9 ± 2.6 vs. 1.7 ± 0.2 kPa), the cell-seeded middle meniscus (MM) hydrogel experienced a 21-fold increase in peak compressive strengths (27.1 ± 4.6 vs. 1.3 ± 0.1 kPa) and a nine-fold increase in initial modulus (6.7 ± 1.6 vs. 0.8 ± 0.1 kPa), the cell-seeded inner meniscus (IM) hydrogel achieved a 22-fold increase in peak compressive strengths (26.0 ± 3.0 vs. 1.2 ± 0.2 kPa) and a nine-fold increase in initial modulus (9.4 ± 1.8 vs. 0.9 ± 0.2 kPa) over the IM hydrogel only ( Wu et al, 2021 ). Ding et al compared the scaffold properties of native meniscus, untreated extracellular matris (ECM) and decellularized ECM (dmECM) from porcine meniscus, and found that both dmECM and untreated ECM scaffolds had lower compressive modulus than native meniscus (181 ± 63 kPa, p < 0.001) and the native meniscus was relatively very stiff and showed significantly higher failure compression stresses (2030 ± 250 kPa, p < 0.001) ( Ding Y. et al, 2022 ). From these two studies, it can be seen that although biological hydrogels can improve the mechanical strength by adding cells, they are still difficult to achieve the mechanical strength of normal meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage tissues were then digested in 0.2% collagenase type II for 8–10 h at 37°C and filtrated through a 70 μm cell strainer. Chondrocytes were expanded in high glucose DMEM supplemented with 10% FBS and 1% penicillin/streptomycin for two passages before cell seeding ( Ding Y et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The porosity of SA, SSP, and SSF scaffolds was determined by the liquid displacement method with pouring cylindrical-shaped scaffolds. 16 Briefly, the diameters (d), heights (h), and weights (m a ) of the dry scaffolds were measured, and the scaffolds were then immersed in 200-proof ethanol. The scaffolds were gently wiped with a paper towel and weighed (m b ) after removal from the ethanol.…”
Section: Preparation Of Sio 2 Nanofibersmentioning
confidence: 99%